In vitro maturation of human oocytes using culture in alginate matrix - Aliakbari, Fereshte; Heidari, Mohammad Hossein; Hossini, Mohammad Ali; Sadeghzadeh, Zahra; Abed, Farhang (Archives of Men’s Health, 2018)
Introduction: In vitro maturation (IVM) infertility treatment in women with infertility problems - for example, polycystic ovary syndrome (PCOS) or ovarian hyperstimulation syndrome (OHSS) reduces the amount of gonadotrophin medications, thereby reducing the cost of treatment. This study aimed to investigate the effect of alginate three-dimensional culture on maturity of immature human oocytes and the amount of 8-cell embryos produced by sperm injection to oocyte cytoplasm (ICSI). Materials and methods: This experimental study was conducted in Mahdieh Infertility Research Center from 2015 to 2017. A total of 70 immature oocytes from the female ovary to candidate for fertilization were selected and divided into two control and experimental groups. In the control group, the basic culture medium (TCM199, FSH 0/75, FBS10 %) and in the experimental group, the basic culture medium with the alginate was used. Then, the mmature oocytes were fertilized by ICSI and 8-cell embryos was evaluated by reverse microscope. Quantitative data was analyzed using the ANOVA statistical method and SPSS software at significant level of a P<0.05. Results: The amount of maturity of immature oocytes to MII metaphase stage and the arrival of the embryos to the 8-cell significantly increased in alginate group compared to the control group (P<0.001). Conclusion: Results demonstrated that alginate can increase the maturity of immature human oocytes and also increases the rate of embryos reaching the 8-cell stage.